A dual process model of popular support for Internet surveillance. (March 2022) - Zhai, Yida; Liu, Yunzhe; Yang, Shuting; Song, Changfa
Abstract: Internet surveillance is prevalent all over the world in this digital era. In particular, governments of authoritarian regimes take much effort to filter and censor information on the Internet. Despite a controlled information environment, a number of people are willing to support Internet censorship by the authorities. This study employs structural equation modeling to examine the relationship between social dominance orientation (SDO) and right-wing authoritarianism (RWA) with supportive attitudes toward Internet censorship. The results show the differential effects of SDO and RWA. Specifically, SDO did not predict people's approval of government censorship on the Internet, whereas RWA had a significant direct effect on it. Both SDO and RWA had an indirect effect on support for Internet censorship through the mediation of meritocratic beliefs. Meritocratic beliefs justify the superiority of government authority and enhance citizens' approval of Internet censorship by governments. There is a trade-off between beliefs in the superiority of meritocracy and beliefs in the rights of ordinary people to learn the truth.